2015
DOI: 10.3390/su71215810
|View full text |Cite
|
Sign up to set email alerts
|

Firm Sustainability Performance Index Modeling

Abstract: Abstract:The main objective of this paper is to bring a model for firm sustainability performance index by applying both classical and Bayesian structural equation modeling (parametric and semi-parametric modeling). Both techniques are considered to the research data collected based on a survey directed to the China, Taiwan, and Malaysia food manufacturing industry. For estimating firm sustainability performance index we consider three main indicators include knowledge management, organizational learning, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
(63 reference statements)
1
12
0
Order By: Relevance
“…Finally, and in coincidence with Wan Mohamed Radzi et al [6], Aguayo and Eames [21], Boyle and Michell [22], Aranda-Usón et al [29], and Xu et al [36] it was identified that, although natural attributes confer distinctive and competitive advantages that can have a positive impact in economic terms on the communities of RAMSAR sites, in practice environmentally reactive plans and temporary solutions are implemented. In that sense, it is considered that the proposed relationships can propitiate continuous equilibrium in the organisations under study.…”
Section: Discussionmentioning
confidence: 76%
“…Finally, and in coincidence with Wan Mohamed Radzi et al [6], Aguayo and Eames [21], Boyle and Michell [22], Aranda-Usón et al [29], and Xu et al [36] it was identified that, although natural attributes confer distinctive and competitive advantages that can have a positive impact in economic terms on the communities of RAMSAR sites, in practice environmentally reactive plans and temporary solutions are implemented. In that sense, it is considered that the proposed relationships can propitiate continuous equilibrium in the organisations under study.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, based on the output of the multivariate normality test, the kurtosis value is 18.69, and this value is not less than 10. Therefore, the multivariate normality hypothesis is rejected [71]. Controlling for outliers and maintaining normal distribution support in adjusting the heterogeneity of the research data.…”
Section: Methodsmentioning
confidence: 99%
“…This Bayesian method facilitates the simultaneous estimation of all cross-loadings, as well as residual correlations in a particular model; however, if ML-based estimation is applied, simultaneous estimation is not possible [18]. In recent years, Bayesian SEM (BSEM) has been applied in different areas like engineering [20], psychology [21,22], and health [23,24].…”
Section: Introductionmentioning
confidence: 99%